2014
DOI: 10.1097/nur.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Knowledge Work of Clinical Nurse Specialists Using a Role Tracking Tool

Abstract: The work of CNSs can be captured and analyzed to enhance understanding of unique and varied CNS contributions in the healthcare matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The practice of CNSs operating as staff members and not attaining supernumerary status, to take on a CNS caseload needs to be addressed in order for CNSs to collaborate and lead the profession 26 . It is recognised that CNSs influence practice through nursing activities, practice development, education, consultation, research and clinical research [27][28][29][30][31][32] . Our findings are similar to Acton Shapiro 33 who highlighted that CNSs are not being utilised to their full extent and are therefore unable to have the desired impact on practice that might be anticipated [33][34] .…”
Section: While Differences May Exist Among Cns Roles/definitions Betwmentioning
confidence: 99%
“…The practice of CNSs operating as staff members and not attaining supernumerary status, to take on a CNS caseload needs to be addressed in order for CNSs to collaborate and lead the profession 26 . It is recognised that CNSs influence practice through nursing activities, practice development, education, consultation, research and clinical research [27][28][29][30][31][32] . Our findings are similar to Acton Shapiro 33 who highlighted that CNSs are not being utilised to their full extent and are therefore unable to have the desired impact on practice that might be anticipated [33][34] .…”
Section: While Differences May Exist Among Cns Roles/definitions Betwmentioning
confidence: 99%
“…In 2012, Richardson and Tjoelker (17) reported a 2.5-year, CNS-led CLABSI reduction initiative that prevented eight CLABSIs, which yielded $200,000 in cost avoidance and saved 1.4 lives. Similarly, Colwill et al (19) identified an association with CNS involvement in care and a reduction in CAUTI rates in the critical care setting. These examples demonstrate the value of the CNS role as an expert clinician, consultant, and change-agent in the prevention of HACs and the associated cost savings for healthcare organizations.…”
Section: Cns Practice and Contributions To Outcomesmentioning
confidence: 87%
“…While clinical nurse specialists (CNSs) roles are recognised internationally (Kilpatrick, Tchouaket, Carter, Bryant‐Lukosius, & DiCenso, ), the role is broad, ambiguous and individualised (Colwill et al., ). Essential components within the CNS role include direct clinical practice, education, consultation, research, professional leadership and ethical decision‐making (Sparacino, ).…”
Section: Introductionmentioning
confidence: 99%
“…CNSs improve practice and service delivery by integrating their specialist knowledge, skill and research evidence (Bryant‐Lukosius et al., ; Lewandowski & Adamle, ), to support evidence‐based practice and improve quality of care (Begley et al., ) and provide safe effective care across a wide range of settings (Newhouse et al., ). CNSs spend varying amounts of time in each component of their role (Colwill et al., ; Kilpatrick et al., ). These variations in time spent within each component of their role may reveal how CNSs adapt their practice and respond to the needs of patients, organisations and health systems (Kilpatrick et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation